Կենսաբարոյագիտությունը՝ որպես միջառարկայական և արժեբանական ուսումնասիրությունների նոր բնագավառ - Սոնա Դավթյան (ՀՀ ԳԱԱ հրատ.)
В статье рассмотрены проблемы разработки целостной концепции биоэтики как системы знаний, формирующейся на стыке социального и биологического познания человека. The article considers problems of development of the holistic concept of bioethics as a system of knowledge emerging at the intersection of social and biological human cognition. The author investigates the origin of bioethics as a science. She comes to conclusion that bioethics is a new field of interdisciplinary and value research.
Keywords: Bioethics